2015
DOI: 10.1007/s12011-015-0504-3
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Trichloride Induces Hypertension and Disturbs the Function of Erythrocyte Membrane in Male Rats

Abstract: Aluminum (Al) is the most abundant metal in the earth's crust. Al accumulates in erythrocyte and causes toxicity on erythrocyte membrane. The dysfunction of erythrocyte membrane is a potential risk to hypertension. The high Al content in plasma was associated with hypertension. To investigate the effect of AlCl3 on blood pressure and the function of erythrocyte membrane, the rats were intragastrically exposed to 0, 64(1/20 LD50), 128(1/10 LD50), and 256(1/5 LD50) mg/kg body weight AlCl3 in double distilled wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…Oxidative stress, lipid peroxidation Kattab et al, 2010;Exley, 2013;Abd-Elhady et al, 2013;Zhang et al, 2016;Yang et al, 2018;Yu et al, 2019 Pro-inflammatory: organ inflammation in lung, intestine, heart, and testis Fogarty et al, 1998;Verma et al, 2007;Lerner, 2007;Exley, 2013;Taiwo, 2014;de Chambrun et al, 2014;Gherardi et al, 2016;Martinez et al, 2017;Hangouche et al, 2017 Immunosupression: induces lymphocyte apoptosis and dysfunction, inhibits lymphocyte proliferation, causes macrophage dysfunction Nordal and Dahl, 1988;Kammalov et al, 2011;She et al, 2012;Zhu et al, 2014;Zhuang et al, 2016;Xu et al, 2018;Yu et al, 2019 Protein denaturation and transformation Exley et al, 2006;Mujika et al, 2018 Enzymatic stimulation or inhibition Ohsaka and Nomura, 2016 Metabolic impairment: impairs glycolysis and Kreb's cycle; promotes lipid and protein oxidation Xu et al 1990;Mailloux et al, 2006 Genotoxicity: reduced cell proliferation and differentiation, dysneurogenesis Nam et al, 2014 Amyloidogenic and anti-amyloidolytic Sakamoto et al, 2006;Xu et al, 2016 Acts as metalloestrogen, promotes proliferation and migration of breast cancer cells Bakir and Darbre, 2015;Darbre, 2016 Induces teratogenesis causing foetal and neonatal defects Malekshah et al, 2005;Wang et al, 2012;El Mazoudy and Bekhet, 2016 Disrupts mineral metabolism of Fe, P, Ca, Zn, Cu by altering intestinal absorption and cellular uptake…”
Section: Toxic Action or Effect Selected Referencesmentioning
confidence: 99%
See 3 more Smart Citations
“…Oxidative stress, lipid peroxidation Kattab et al, 2010;Exley, 2013;Abd-Elhady et al, 2013;Zhang et al, 2016;Yang et al, 2018;Yu et al, 2019 Pro-inflammatory: organ inflammation in lung, intestine, heart, and testis Fogarty et al, 1998;Verma et al, 2007;Lerner, 2007;Exley, 2013;Taiwo, 2014;de Chambrun et al, 2014;Gherardi et al, 2016;Martinez et al, 2017;Hangouche et al, 2017 Immunosupression: induces lymphocyte apoptosis and dysfunction, inhibits lymphocyte proliferation, causes macrophage dysfunction Nordal and Dahl, 1988;Kammalov et al, 2011;She et al, 2012;Zhu et al, 2014;Zhuang et al, 2016;Xu et al, 2018;Yu et al, 2019 Protein denaturation and transformation Exley et al, 2006;Mujika et al, 2018 Enzymatic stimulation or inhibition Ohsaka and Nomura, 2016 Metabolic impairment: impairs glycolysis and Kreb's cycle; promotes lipid and protein oxidation Xu et al 1990;Mailloux et al, 2006 Genotoxicity: reduced cell proliferation and differentiation, dysneurogenesis Nam et al, 2014 Amyloidogenic and anti-amyloidolytic Sakamoto et al, 2006;Xu et al, 2016 Acts as metalloestrogen, promotes proliferation and migration of breast cancer cells Bakir and Darbre, 2015;Darbre, 2016 Induces teratogenesis causing foetal and neonatal defects Malekshah et al, 2005;Wang et al, 2012;El Mazoudy and Bekhet, 2016 Disrupts mineral metabolism of Fe, P, Ca, Zn, Cu by altering intestinal absorption and cellular uptake…”
Section: Toxic Action or Effect Selected Referencesmentioning
confidence: 99%
“…The activities of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and glutathione (GSH) are affected by Al exposure because of oxidative stress (Oteiza et al, 1993a;Julka and Gill, 1996;Campbell et al, 1999). Abnormal increases in levels of malondealdehyde (MDA) and thiobarbituric acid reactive substances (TBARS) were reported along with decreased levels of antioxidants such as GSH, GPx, SOD, and CAT in tissue homogenates of rats exposed to Al (Anane and Creppy, 2001;Gonzalez et al, 2007;Newairy et al, 2009;Khattab et al, 2010;Bai et al, 2012;Exley, 2013;Abd-Elhady et al, 2013;Zhang et al, 2016;Yu et al, 2019).…”
Section: Toxic Action or Effect Selected Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Various concentrations of aqueous solutions of tris acetylacetonate aluminium (III) (Al (acac) 3 , tris maltolate aluminium (III) (Al(malt) 3 and tris aluminium lactate (Al(lac) 3 ) caused erythrocytes to be osmotically fragile (Zatta et al, 1989). Treatment of rat erythrocytes with aluminium chloride caused increased osmotic fragility due to increased lipid peroxidation (Gutteridge et al, 1995;Hernández et al, 2008;Al-Qayim et al, 2014;Oztürk & Ozdemir, 2015;Zhang et al, 2016). However, Bazzoni et al (2005) reported improved stability of erythrocyte membrane and reduced erythrocyte size and aggregation in adult male rats after parenteral treatment with aluminium hydroxide.…”
Section: Metalsmentioning
confidence: 99%